Intravenous aminophylline in patients admitted to hospital with non-acidotic exacerbations of chronic obstructive pulmonary disease: a prospective randomised controlled trial - Duffy, N (BMJ Group, 2005)
Background: Intravenous aminophylline is commonly used in the treatment of exacerbations of chronic obstructive pulmonary disease (COPD), despite limited evidence for its efficacy and known risks of toxicity. We hypothesised that adding intravenous aminophylline to conventional treatment would not produce clinically important changes in the speed of spirometric or symptomatic recovery or shorten hospital stay in patients with exacerbations of COPD. Methods: Eighty patients admitted to hospital with non-acidotic exacerbations of COPD were recruited at admission to a randomised, double blind, placebo controlled study comparing intravenous aminophylline 0.5 mg/kg/hour after an appropriate loading dose with an equivalent volume of 0.9% saline. The primary outcome was the change in post-bronchodilator forced expiratory volume in 1 second (FEV(1)) over the first 5 days of the admission. Secondary end points were changes in self-reported breathlessness, arterial blood gas tensions, forced vital capacity (FVC), and length of hospital stay. Results: There was no difference in the post-bronchodilator FEV(1) over the first 5 days between the aminophylline and placebo groups. In the aminophylline group, 2 hours of treatment produced a small but significant rise in arterial pH (p = 0.001) and a fall in arterial carbon dioxide tension (p = 0.01) compared with placebo treatment. There were no differences in the severity of breathlessness, post-bronchodilator FVC, or length of hospital stay between the groups. Nausea was a more frequent side effect in the aminophylline group (46% v 22%; p<0.05), but palpitations and headache were noted equally in both groups. Conclusions: Although intravenous aminophylline produced small improvements in acid-base balance, these did not influence the subsequent clinical course. No evidence was found for any clinically important additional effect of aminophylline treatment when used with high dose nebulised bronchodilators and oral corticosteroids. Given its known toxicity, we cannot therefore recommend the use of intravenous aminophylline in the treatment of non-acidotic COPD exacerbations.